Good Corporate Governance and Leverage of Financial Performance: Literatur Review - Syafa’ah, Lailis (IPTEK Journal of Proceedings Series, 2020)
A company has a main target to make a profit. However, in these years there are some private company and State-Owned Enterprises has financial trouble and suffered financial losses. Some of those financial trouble is caused by chaotic management and high ratio of debt that causing the risk of failed paying. Successful corporation management is strongly related with applying good corporate governance (GCG). This research aim to analyze the impact of good corporate governance (boards of commissioners, boards of independent commissioners, boards of directors, institutional ownerships) as non-financial aspect and leverage as financial aspect of financial performance. This research is a qualitative research using theoretical review and supported by the previous research. There are two theories as the basic theories to observing the previous research which is agency and trade off theory. The result of the analysis of some previous research found some proposition: (1) boards of commissioners has impact to financial performance, (2) boards of independent commissioners has impact to financial performance, (3) boards of directors has impact to financial performance, (4) institutional ownerships has impact to financial performance, and (5) leverage has impact to financial performance